Surgical treatment of primary intracranial and extracranial communicating leiomyosarcoma: a case report - Pu, Kuairong; Wang, Tianhong; Li, Zhe; Lin, Xiwen; Wu, Jun; Shao, Dongchuan; Zhao, Nan (Frontiers in Oncology, 2025)
Primary intracranial-extracranial communicating leiomyosarcomas, capable of invading both intracranial and extracranial regions and involving complex anatomical structures, are exceedingly rare neoplasms. We present the case of a 37-year-old male initially presented with a subcutaneous mass on the left frontal vertex. Post-surgical intervention, a recurrent lump emerged on the left frontotemporal vertex. Symptoms, computed tomography (CT), and magnetic resonance imaging (MRI) revealed a mass on the left frontal vertex accompanied by an irregular abnormal lesion. Leiomyosarcoma diagnosis was confirmed on both occasions. The patient underwent leiomyosarcoma excision under general anesthesia. Recurrence was noted 2 years and 4 months post-surgery, necessitating an expanded excision. After 2 years of follow-up, no significant complications were observed, and the patient’s condition remains stable. Primary extracranial communicating leiomyosarcoma is exceptionally rare, with surgery as the primary treatment modality. The decision to excise the lesion should consider the patient’s age, tumor location, pathological features, and presence of distant metastases.